Using the Helmert-transformation to reduce dimensionality in a mixed model: Application to a wage equation with worker and firm heterogeneity - Øivind Anti Nilsen; Arvid Raknerud; Terje Skjerpen (Institute for the Study of Labor (IZA), 2011)
A model for matched data with two types of unobserved heterogeneity is considered - one related to the observation unit, the other to units to which the observation units are matched. One or both of the unobserved components are assumed to be random. This mixed model allows identification of the effect of time-invariant variables on the observation units. Applying the Helmert transformation to reduce dimensionality simplifies the computational problem substantially. The framework has many potential applications; we apply it to wage modeling. Using Norwegian manufacturing data shows that the assumption with respect to the two types of heterogeneity affects the estimate of the return to education considerably.
urn:nbn:de:101:1-201107283736
Keywords: C23; C81; J31; 330; high-dimensional two-way unobserved components; matched employer-employee data; ECM-algorithm